Peran Media Sosial Sebagai Media dalam Menyebarkan Bullying dan Diskriminasi: Studi Kasus Menfess UB - Juang, Amos; Pambudi, Brahmantio Jati; Tanugroho, Christopher Robin; Suryanto, Frederick Rainer (Majalah Ilmiah METHODA, 2024)
The purpose of this research is to investigate the role of social media in spreading bullying and discrimination, particularly through the Menfess UB Twitter account at Brawijaya University, Malang. This research aims to understand the extent to which social media influences students towards bullying and awareness of  respecting diversity to prevent such behavior. This study uses a  quantitative method, including using an online survey to answer the questions. The results indicate that while social media can be a tool for negative behavior, many students are aware of its impacts and understand the importance of diversity and respect. However, instances of bullying and discrimination still occur, highlighting the need for more effective preventive measures.